2020
DOI: 10.1136/bmjopen-2019-034921
|View full text |Cite
|
Sign up to set email alerts
|

Elastic-band resistance exercise or vibration treatment in combination with hydroxymethylbutyrate (HMB) supplement for management of sarcopenia in older people: a study protocol for a single-blinded randomised controlled trial in Hong Kong

Abstract: IntroductionSarcopenia is a geriatric syndrome characterised by progressive loss of skeletal muscle mass and function with risks of adverse outcomes and becomes more prevalent due to ageing population. Elastic-band exercise, vibration treatment and hydroxymethylbutyrate (HMB) supplementation were previously proven to have positive effects on the control of sarcopenia. The purpose of this study is to evaluate the effectiveness of elastic-band exercise or vibration treatment with HMB supplementation in managing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…A review of Clinical Trials showed that HMB supplementation is essential for the maintenance of muscle mass in the elderly over 65 years old, especially the elderly who are bedridden or sedentary, and contributes to the reduction of muscle metabolism. Many studies have shown that HMB increased muscle mass and strength in older people with reduced lean body mass ( 100 – 102 ). In addition, studies have shown that HMB supplementation has a positive effect on lowering plasma cholesterol and blood pressure, thereby reducing the risk of cardiovascular disease ( 103 105 ).…”
Section: Joint Intervention Of Sarcopenia and Cvdsmentioning
confidence: 99%
“…A review of Clinical Trials showed that HMB supplementation is essential for the maintenance of muscle mass in the elderly over 65 years old, especially the elderly who are bedridden or sedentary, and contributes to the reduction of muscle metabolism. Many studies have shown that HMB increased muscle mass and strength in older people with reduced lean body mass ( 100 – 102 ). In addition, studies have shown that HMB supplementation has a positive effect on lowering plasma cholesterol and blood pressure, thereby reducing the risk of cardiovascular disease ( 103 105 ).…”
Section: Joint Intervention Of Sarcopenia and Cvdsmentioning
confidence: 99%
“…Of the 27 studies on resistance exercises, 9 studies ( n = 9) used repetition maximum (RM) criteria [ 18 , 25 , 27 , 29 , 30 , 32 , 36 , 37 , 40 ], whereas 10 studies ( n = 10) used rating of perceived exertion (RPE) [ 15 , 19 , 21 , 23 , 26 , 28 , 31 , 38 , 39 , 41 ] criteria to quantify the intensity of resistance training. One study each ( n = 1) used OMNI-RES scale (OMNI-Rating of perceived Exertion scale) [ 34 ], heart rate reserve criteria [ 20 ] or coach-adjusted resistance criteria [ 24 ], and maximal theoretical force [ 33 ] while four studies ( n = 4) [ 16 , 17 , 22 , 35 ] did not report the method used for intensity measurement. The percentage of 1RM, which ranged from 20 to 80% of 1RM, was used by all the nine studies that used RM criteria, and of the 10 studies ( n = 10) that used RPE, it ranged from 6 to 14 points.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by 2050, there will be 426 million older people, up from 143 million in 2019. Increasing geriatric populations lead to a rise in sarcopenia, a geriatric syndrome characterized by progressive loss of skeletal muscle mass and function [ 25 ]. Developing a nomenclature for aging-related skeletal muscle degeneration was a major step towards reaching international consensus on the issue in 2016 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%